Model Kompensasi, Lingkungan Kerja dan Komitmen Afektif Organisasi sebagai Variabel Intervening terhadap Kinerja Sumber Daya Manusia: Studi pada PT. Komipo Pembangkitan Jawa Bali di Jepara - Ikhsan Toga Kharismawan; Ibnu Khajar (Economic Reviews Journal, 2024)
This study aims to identify the impact of compensation and non-physical work environment on employee performance, with affective commitment as an intervening variable. The population of this study consists of permanent and non-permanent employees of PT. Komipo PJB. A sample of 100 respondents was determined using Maximum Likelihood (ML) estimation with purposive sampling. Data analysis using SMART-PLS revealed that compensation has a positive and significant impact on affective commitment and employee performance. The non-physical work environment has a positive but insignificant effect on affective commitment, yet it positively and significantly influences employee performance. Interestingly, affective commitment was found to have a negative and significant relationship with employee performance.